Magnetically recoverable ZrO2/Fe3O4/chitosan nanomaterials for enhanced sunlight driven photoreduction of carcinogenic Cr(vi) and dechlorination & mineralization of 4-chlorophenol from simulated waste water. Issue 16 (3rd February 2016) - Kumar, Amit; Guo, Changsheng; Sharma, Gaurav; Pathania, Deepak; Naushad, Mu; Kalia, Susheel; Dhiman, Pooja
Abstract : In this laboratory-scale experiment we report the treatment of carcinogenic Cr(vi ) and 4-chlorophenol by ferromagnetic ZrO2 /Fe3 O4 nano-heterojunctions supported on chitosan. Abstract : In this laboratory-scale experiment we report the treatment of carcinogenic Cr(vi ) and 4-chlorophenol by ferromagnetic ZrO2 /Fe3 O4 nano-heterojunctions supported on chitosan. A combination of different semiconductors with different photo-activities has proven to be a tested and effective technique for harnessing solar light in waste water treatment. The prepared heterojunction and its composite with chitosan has been characterized by X-Ray Diffraction (XRD), Fourier Transform Infra Red spectroscopy (FTIR), High Resolution Transmission Electron Microscopy (HRTEM), Small Area Electron Diffraction (SAED), Vibrating Sample Magnetometry (VSM), Energy Dispersive X-ray analysis (EDX), UV-visible spectrophotometry and Brunauer–Emmet–Teller surface area analysis (BET). Treatment of chlorophenols is challenging because of their hydrophobicity and stability. In our study we have reported excellent results for the dechlorination of 4-chlorophenol and the results were analyzed in terms of Liquid Chromatography-Mass Spectrometry (LC-MS), Chemical Oxygen Demand analysis (COD) and emission. 88.6% of 4-CP degradation was achieved in the presence of ZrO2 /Fe3 O4 /chitosan in 3 h under sunlight and a reduction of 90.2% for Cr(vi ) was obtained. The heterojunction formation leads to charge separation and decreased recombination of charge carriers. The synergistic effects of charge separation in the heterojunction, alcohols, peroxide, magnetism and adsorption with essential explanation of mechanisms make this study important and promising.